2017
DOI: 10.15694/mep.2017.000022
|View full text |Cite
|
Sign up to set email alerts
|

Stress Level Assessment of Medical School Program and correlations between Learning Styles and Teaching Methodologies

Abstract: Stress is a psychological change that is becoming ever more frequent among medical school students than that of the general population, and these stress levels may affect academic performance. When the individual learning style does not fit into the method used by the student's university, the clash may become another stress factor. We evaluated preferred learning styles (Honey-Alonso Learning Styles Questionnaire) and stress levels (Lipp Inventory of Stress Symptoms for Adults) among medical students from two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…Various studies have also reported differences in stress levels between genders with a greater prevalence of stress among women in a previous study by our team and in studies by other researchers (Botelho et al, 2017;Tempski et al, 2012).…”
Section: Introductionsupporting
confidence: 63%
“…Various studies have also reported differences in stress levels between genders with a greater prevalence of stress among women in a previous study by our team and in studies by other researchers (Botelho et al, 2017;Tempski et al, 2012).…”
Section: Introductionsupporting
confidence: 63%
“…The active methodology of teaching can cause anxiety in students [ 10 ]. It is known that students who enter medical schools whose teaching methodologies differ from those experienced in elementary education have a great chance of developing stress and anxiety compared with students who enter schools with conventional teaching methods [ 11 ]. However, when comparing two Brazilian medical schools with different teaching methodologies, Botelho et al [ 11 ] perceived that stress levels were high in both schools, with prevalence rates above 65%.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that students who enter medical schools whose teaching methodologies differ from those experienced in elementary education have a great chance of developing stress and anxiety compared with students who enter schools with conventional teaching methods [ 11 ]. However, when comparing two Brazilian medical schools with different teaching methodologies, Botelho et al [ 11 ] perceived that stress levels were high in both schools, with prevalence rates above 65%. With the evolution of the active course, better adaptation and understanding of the teaching method were observed, leveraged by the factors of proximity with the facilitator professor, the use of real clinical cases, study in small groups, and the help of a tutor in the organization and orientation of the learning, but without any perception of improvement of the symptoms of burnout [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Frequent examinations,11 lengthy academic curricula,12 tiered, rather than pass/fail grading systems,13 a mismatch between preferred teaching and learning styles14 and lack of preparation for career transitions, in particular between preclinical and clinical training15 have all been associated with poorer mental health outcomes in medical students. The structure of medical school curricula therefore offers a significant opportunity for intervention 16…”
Section: Introductionmentioning
confidence: 99%